2019
DOI: 10.1177/2332858419867692
|View full text |Cite
|
Sign up to set email alerts
|

Academic Harms of Missing High School and the Accuracy of Current Policy Thresholds: Analysis of Preregistered Administrative Data From a California School District

Abstract: Currently, the state of California has dedicated much focus to reducing absenteeism in schools through the In School + On Track initiative, which revitalizes efforts made to keep accurate and informative attendance data. Additionally, absenteeism has been integrated into California’s Local Control and Accountability Plan to monitor district performance and improvement. Given the heightened policy concern surrounding absenteeism and truancy, this study seeks to improve researchers’ understanding of the impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…In Charlotte, North Carolina, a 19-year-old boy was arrested by ICE on his way to high school, demonstrating yet another case in which enforcement is utilizing schools to corral students who are not legal citizens (Price, 2016). In light of the established relationship between absenteeism and many short- and long-term outcomes for students (Balfanz & Byrnes, 2006; Gottfried, 2010; Gottfried & Kirksey, 2017; Kirksey, 2019), fear of coming to school may interconnect with the achievement gaps also shown to be exacerbated in this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In Charlotte, North Carolina, a 19-year-old boy was arrested by ICE on his way to high school, demonstrating yet another case in which enforcement is utilizing schools to corral students who are not legal citizens (Price, 2016). In light of the established relationship between absenteeism and many short- and long-term outcomes for students (Balfanz & Byrnes, 2006; Gottfried, 2010; Gottfried & Kirksey, 2017; Kirksey, 2019), fear of coming to school may interconnect with the achievement gaps also shown to be exacerbated in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Less research has focused specifically on the consequences of enforcement on student absenteeism, although media coverage has shown substantial effects, at least in the short term (Blitzer, 2017(Blitzer, , 2018. In one study using data from the Early Childhood Longitudinal Study: Kindergarten Class of 2010-11, Sattin-Bajaj and Kirksey (2019) found that an increase in the number of apprehensions by a child's nearest immigration enforcement jurisdiction was associated with a decrease in absenteeism in kindergarten. They interpret this finding to suggest that under certain conditions-specifically when immigration enforcement policies are guided by humanitarian concerns, such as family ties in the United States, which was the case in the latter part of Obama's second term-schools may be perceived by families as sanctuaries, at least for children in kindergarten.…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…With regard to academics, research has clearly established the relationship between absenteeism and lower performance on standardized assessments, with many of these studies employing a strong causal design (Gershenson et al, 2017; Goodman, 2014; Gottfried, 2009, 2010, 2011; Easton & George, 1982; Gottfried & Kirksey, 2017; Moonie et al, 2008; Roby, 2004). Aside from test scores, another concern is that students who miss school are also more at-risk for being held back, dropping out of high school, and becoming unemployed following graduation (Alexander et al, 1997; Barrington & Hendricks, 1989; Broadhurst et al, 2005; Kirksey, 2019; Neild & Balfanz, 2006; Rumberger, 1995; Rumberger & Thomas, 2000). Gottfried (2014) also found evidence of lower levels of social development and higher levels of school disengagement.…”
mentioning
confidence: 99%
“…Analysis of preregistered administrative data from a California school district" (Kirksey, 2019) • "Save your strokes: Chinese handwriting practice makes for ineffective set of instructional time in second language classrooms" (Lu et al, 2019) • "Experimental evidence on the effects (or lack thereof) of informational framing during the college transition" (Kramer, 2020) • "Smart but evil? Student-teachers' perception of educational researchers' epistemic trustworthiness" (Merk & Rosman, 2019) • "Effect of local norms on racial and ethnic representation in gifted education" (Peters et al, 2019) • "Taking it to the next level: A field experiment to improve instructor-student relationships in college" (Robinson et al, 2019) Four of the studies in the special series used a group experimental design, whereas three studies were secondary data analyses.…”
Section: Registered Reports 16mentioning
confidence: 99%